Comparative Analysis on Liquidity and Risk-Taking Behaviour between Islamic and Conventional Banks in MENA Region - Salihu Liman Mairafi; Sallahuddin Hassan; Shamsul Bahrain Mohamed-Arshad (Universitas Muhammadiyah Yogyakarta, 2022)
We compare the effect of liquidity on risk-taking between Islamic and conventional banks in the MENA region over the period 2005-2017. Using the fixed effect panel model with panel-corrected standard error, we found that funding liquidity in both Models significantly affects conventional banks' risk-taking behaviour, but the effect on the Islamic counterpart is insignificant. However, liquidity risk and bank activities represented by loans significantly affect Islamic bank risk-taking behaviour but show no significant effect on conventional banks. However, the effect varies with risk-taking proxies and the size of banks. This entails liquidity and bank risk-taking behaviour that differs with the type of banking system and the countries’ peculiarities. Thus, liquidity regulation should be implemented with the consideration of other region and their peculiarities.